Preventing Bullying in Schools: How do Islamic Religious Teachers Respond? - Pasaleron, Roni; Asril, Zainal; Tuncer, Eyyup; Jaafar, Azhar; Rustiya, Rustiya; Rosmerina, Rosmerina (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2023)
The phenomenon of bullying cases among students in schools has significantly increased in Indonesia. It has become a trending topic in daily news in various national media both related to the perpetrators and victims of the bullying. Islamic religious education teachers should also be responsible to educate learners to behave based on religious values believed as an alternative to prevent bullying behavior. The study is aimed at identifying how Islamic religion teachers should participate in preventing bullying among students. This study employs a qualitative method of a phenomenological approach. The data was collected through in-depth individual interviews and group discussions with thirty informants consisting of fifteen Islamic religious education teachers, five principals, five parents and five students in fifteen elementary schools in one of the provinces in Indonesia. To enrich the main data, the author also conducted a direct observation related to how the actions taken by teachers in preventing bullying. All interview and observation data were thematically analyzed using the Miles and Huberman interactive analysis model assisted by NVivo software. The research findings reveal five themes of Islamic religion teachers' attitudes in preventing bullying among students: i) instilling mutual respect among students, ii) modeling how to get along based on religious values, iii) thematically linking all religious subject matter to prevent bullying behavior, iv) socializing the adverse effects of bullying to the victims, v) working with all school members to develop work strategies to prevent bullying, vi) involving parents as ambassadors of children without bullying behavior. These six attitudes are real examples of how religious teachers respond to prevent bullying.